Investigation of Substituent Effects on Corrosion Protection of Mild Steel by Schiff Bases in 0.5 M NaCl - Athirah Dzolin, Syaidah; Bahron, Hadariah; Mohd, Yusairie (International Journal of Engineering and Technology, 2018)
Three Schiff bases, namely (E)-2-methoxy-6-((phenylimino)methyl) phenol (A1), (E)-2-(((4-chlorophenyl)imino)methyl)-6-methoxyphenol (A2) and (E)-2-(((4-bromophenyl)imino)methyl)-6-methoxyphenol (A3), were synthesised via condensation reaction between o-vanillin and derivatives of aniline. The structures were elucidated through spectral and physicochemical techniques of melting point, elemental analysis (C, H and N), 1H Nuclear Infrared (IR) spectroscopy, Magnetic Resonance (NMR) and UV-Visible Spectroscopy. The distinctive ï®(C=N) were observed in range of 1610-1613 cm-1 while ï¤(OH) peaks appeared between 13.37-13.44 ppm. 0.05 M solutions of the Schiff bases were prepared in 0.3 M aqueous NaOH solution prior to depositing on mild steel using cyclic voltammetry (CV) technique, forming brownish coloured Schiff base coatings. The corrosion behaviour of coated and uncoated mild steel was studied using Tafel Extrapolation Method (TEM) in 0.5 M NaCl. The mild steel coated with A1 showed the highest inhibition efficiency (I.E.) of 84.81%, hence indicating a superior surface coverage, followed by A2 and A3 with 67.48% and 54.82 % I.E., respectively.Â Â Â